The Agony of Choice? Preserved Affective Decision Making in Early Multiple Sclerosis - Landmeyer, Nils C.; Dzionsko, Inga; Brockhoff, Laura; Wiendl, Heinz; Domes, Gregor; Bölte, Jens; Krämer, Julia; Meuth, Sven G.; Johnen, Andreas (Frontiers in Neurology, 2020)
Background: Cognitive impairment (CI) is an early and frequent symptom of multiple sclerosis (MS). Likewise, affective symptoms (e.g., depression and anxiety) and alterations in the processing of emotional stimuli have been frequently reported. Thus, abilities that integrate affective and cognitive processes such as decision making (DM) based on affective feedback are potentially valuable early diagnostic markers for MS. The available research on this topic, however, is still inconclusive and suffers from methodological issues. Methods: We compared DM ability in a clinically homogeneous cohort of 24 patients with early relapsing–remitting MS (RRMS) and 59 age-matched healthy controls (HCs). A modified version of the Iowa gambling task (IGT) allowed us to control for individual differences in search strategies during the risk exploration phase. Besides standard IGT measures (netscore, obtained play money, and learning index), we also examined reaction times and post-error slowing (PES) patterns as a proxy for abnormalities in the processing of affective feedback. Results: The performance of patients did not significantly deviate from HCs in any standard parameter of the modified IGT. Furthermore, although RRMS patients reacted significantly slower than HCs overall, we found similar patterns of PES in both groups, suggesting similarly efficient processing of affective feedback. Conclusion: We conclude that there is no specific deficit in affective feedback processing in early RRMS. Previous findings of IGT impairments in this patient group may thus not represent a genuine deficit in affective DM but rather be related to sample characteristics, general CI, and/or differences in individual search strategies. Future research should explore the potential influence of lesion volumes and locations on DM ability by employing brain imaging techniques.